Influence of Zinc, Vitamin A and Magnesium Supplements on the Thyroid Function in Hypothyroidism Patients - Misbah Arshad; Muntaha Jaffar; Farah Khanum; Noor Fatima; Alina Akbar; Ghulam Rubab (Contemporary Research and Perspectives in Biological Science Vol. 9, 2025)
Background: An inadequate thyroid hormone synthesis slows down the body’s metabolism and causes a host of crippling symptoms, such as weight gain, weariness, cold sensitivity, and cognitive decline. Hypothyroidism is a common endocrine illness. Hormone replacement medication is the usual treatment for hypothyroidism, but new research indicates that shortages in some micronutrients, including zinc, vitamin A, and magnesium, may be important in the development and course of the condition. Supplementing these micronutrients could be an adjuvant approach in the treatment of thyroid dysfunction because they are necessary to produce thyroid hormones, metabolism, and immunological regulation. Objective: The purpose of this study is to look at the potential therapeutic effects of magnesium, zinc and vitamin A supplements on oxidative stress, inflammatory markers and thyroid function in people with hypothyroidism. The goal of the study is to ascertain whether treating deficits in these micronutrients can boost thyroid hormone production, reduce symptoms, and strengthen the immune system and metabolism in individuals with hypothyroidism. Methods: A detailed review of peer-reviewed literature, including clinical trials, observational studies, and meta-analyses, was conducted to explore the role of zinc, vitamin A, and magnesium in thyroid health. The studies selected for review included both placebo-controlled interventions and observational data on micronutrient supplementation in hypothyroid patients. Key variables such as serum levels of thyroid hormones (TSH, FT3, FT4), oxidative stress markers (hs-CRP, MDA), and overall clinical outcomes were analysed to assess the effects of supplementation. Results: The review emphasised a constant positive relationship between better thyroid function and supplementing with zinc, vitamin A, and magnesium. It has been discovered that taking zinc supplements helps boost thyroid hormone synthesis by improving free and total thyroxine (T4) levels and improving TSH regulation. The antioxidant qualities of vitamin A have been found to lower oxidative stress and stabilise thyroid function; on the other hand, magnesium supplementation has improved energy metabolism and decreased inflammatory indicators. Overall, the patients who received these micronutrients showed changes in the balance of thyroid hormones, reduced inflammation, and improved metabolic function, all of which point to important therapeutic advantages. Conclusion: In summary, the results highlight the possible function of magnesium, zinc, and vitamin A supplements in the treatment of hypothyroidism. These micronutrients assist in reducing inflammation and oxidative stress, which are frequently linked to thyroid diseases, in addition to aiding in the production and control of thyroid hormones. Patients with hypothyroidism who take these supplements as part of their treatment plan, especially if they have known deficits, may experience a better quality of life and more efficient symptom management. It is advised that larger sample sizes and longer trial lengths be used in future clinical studies to confirm the effectiveness of this strategy and provide standardized procedures for micronutrient supplementation in hypothyroid treatment.